2019
DOI: 10.1080/09513590.2019.1653564
|View full text |Cite
|
Sign up to set email alerts
|

Does subclinical hypothyroidism and/or thyroid autoimmunity influence the IVF/ICSI outcome? Review of the literature

Abstract: While overt hypothyroidism is a well-known risk factor for infertility, the association of subclinical hypothyroidism (SCH) or thyroid autoimmunity and reproductive failure has been still not elucidated. In this literature review, the current data on the effect of SCH and/or thyroid autoimmunity and human reproduction is presented. The main ART outcome measures are as follows: number of oocytes retrieved, fertilization rate, implantation rate, clinical pregnancy rate per embryo transfer, embryo quality, miscar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…On the other hand, there were studies failed to show any significant difference between the anti-TPO+ and anti-TPO− group with respect to live birth delivery, pregnancy or miscarriage, and the same results were presented when comparing subgroups according to TSH level (15). LT4 supplementation should be recommended to improve clinical pregnancy outcomes in women with thyroid dysfunction, and in infertile women with SCH and/or TAI who are undergoing IVF, mostly to reduce the miscarriage rate (16). Mature (MII) oocytes from women undergoing IVF contain thyroid hormone (TR) 1, TR 2, TR 1 and TR 2 mRNA, suggesting a possible direct effect of triiodothyronine (T3) on the human oocyte (17).…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, there were studies failed to show any significant difference between the anti-TPO+ and anti-TPO− group with respect to live birth delivery, pregnancy or miscarriage, and the same results were presented when comparing subgroups according to TSH level (15). LT4 supplementation should be recommended to improve clinical pregnancy outcomes in women with thyroid dysfunction, and in infertile women with SCH and/or TAI who are undergoing IVF, mostly to reduce the miscarriage rate (16). Mature (MII) oocytes from women undergoing IVF contain thyroid hormone (TR) 1, TR 2, TR 1 and TR 2 mRNA, suggesting a possible direct effect of triiodothyronine (T3) on the human oocyte (17).…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, Yamamoto JM et al [24] in a systematic review and meta-analysis of randomized controlled trials found no benefit of therapy on obstetric, neonatal, childhood intelligent quotient (IQ) or neurodevelopmental outcomes and they concluded that currently, there was no evidence to support the treatment of subclinical hypothyroidism diagnosed in pregnancy. Moreover, the role of subclinical hypothyroidism and thyroid autoimmunity on assisted reproductive technology (ART) success rate was recently found to be controversial [25]. Our patients did not receive treatment with Levo-thyroxine.…”
Section: Discussionmentioning
confidence: 93%
“…We performed ICSI procedure for all patients but we observed only a tendency on embryo quality in favor of ATA-negative cases (p = 0.09). Safarian et al have also concluded that ICSI procedure is a preferred method in women with positive ATA [30].…”
Section: Discussionmentioning
confidence: 97%